So-called gray zone between athlete’s heart and hypertrophic cardiomyopathy- the significance of new imaging techniques in differential diagnosis - Fałkowska, Urszula; Radzka, Agnieszka; Pawlicka, Marta; Mroczek, Anna; Bałabuszek, Kamil; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Background Athlete’s heart characterized many adaptive changes in the heart in response to physical exertion. The discovery of the "heart of the athlete" phenomenon was made by Henschen already at the end of the 19th century during physical examination through percussion the chest of cross-country skiers. The aim of the study The aim of the paper is to present new imaging techniques aimed at more accurate diagnosis of the differential heart of patients with physiological adaptation to intense physical exercise of left ventricular hypertrophy and patients with hypertrophic cardiomyopathy. Material and method Standard criteria were used to review the literature data. The search of articles in English in the PubMed and Google Scholar database was carried out using the following keywords: athlete’s heart, hypertrophic cardiomyopathy, tissue doppler method, magnetic resonance (MR) T1, extracellular volume (ECV) mapping, three-dimensional echocardiography (3D). Description of the state of knowledge Athlete’s heart may occasionally imitate pathological conditions related to sudden death, such as hypertrophic cardiomyopathy — the leading cause of sudden cardiac death in young athletes. Problems in differential diagnosis between the athlete’s heart and hypertrophic cardiomyopathy are still existed. In the aspect of the differentiation of adaptive and pathological left ventricular hypertrophy in athletes, the diagnostic problem concerns the thickness of the myocardium (especially the interventricular septum) within 13-16 mm and constituting the so-called gray zone. This is a range of values that can be an expression of physiological LVH in competitive athletes and the symptom of a mild phenotype HCM. Summary This kind of lesions require an extended cardiac diagnosis, these include: echocardiography, tissue doppler imaging, cardiovascular magnetic resonance T1, extracellular volume and 3D echocardiography.